An Exploration of New Nursing Graduate and Experienced Nurse Mentorship Pairing Processes: A Multi-Method Approach - Devey, Robin (Université d'Ottawa / University of Ottawa, 2020)
Background Mentorship is used to ease entry to practice for new nursing graduates. However, little is known about the process of pairing with experienced nurses. The aim of this dissertation is to explore mentorship pairing processes for new nursing graduates and experienced nurses. Methods 1. A quality improvement project was conducted using organizational data to describe the impact of the New Graduate Guarantee program at The Ottawa Hospital from 2013 to 2018 on new graduate nurses and organizational outcomes. 2. An interpretive descriptive study was conducted to develop an in-depth understanding of mentorship pairing practices specific to nursing occurring in a clinical setting that will ultimately inform future mentorship pairing practices. 3. A systematic review was conducted to determine the effect of mentorship pairing processes on the mentoring relationship and outcomes at the level of the new nursing graduate, mentor and organization. Findings 1. From 2013 to 2017, 66 nurses were hired directly into operational vacancies and 579 new graduate nurses were paired with a mentor in the New Graduate Guarantee program. The two-year turnover rate for new graduates who participated in the New Graduate Guarantee program (21.5%, N=92/427) was lower than new graduate turnover rates reported in the literature. 2. Interviews with 13 new graduate nurses and 12 mentors revealed a lack of awareness of current nursing mentorship pairing processes. Six nurse leaders described pairing processes using third party pairing. Participants suggested preparation, socialization and self-selection are key components to consider for future practice. 3. Of 2583 citations screened, no studies evaluated the nursing mentorship pairing process. Research is required to determine effective mentorship pairing processes in nursing. Conclusion Although 579 nurses were hired through the New Graduate Guarantee nursing mentorship program, the 13 new graduates and 12 mentors interviewed were unaware of the process used for pairing. Furthermore, no studies have evaluated mentorship pairing processes. Ninety percent of new graduates hired participated in the New Graduate Guarantee program. Future research is required to trial pairing processes proposed by nurse leaders, new graduates and experienced nurses and to develop and validate tools to evaluate the outcomes of these pairings.
Keywords: Mentorship; Pairing Process; New Nursing Graduate; Mentor; Nursing Leadership; Multi-method; Quality Improvement; Qualitative Study; Systematic Review